2002
DOI: 10.1097/00000539-200203000-00020
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the INVOS 4100 and the NIRO 300 Near-Infrared Spectrophotometers

Abstract: Near-infrared spectroscopy (NIRS) has been proposed as a noninvasive clinical method for assessing cerebral oxygenation. The acceptable reliability and validity of NIRS values have not been established despite their widespread use. The INVOS 4100 and the NIRO 300 can display cerebral oxygen saturation as regional cerebral oxygen saturation and tissue oxygenation index, but they produce differing results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
88
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(96 citation statements)
references
References 16 publications
8
88
0
Order By: Relevance
“…Besides continuous electroencephalogram monitoring, cranial ultrasound, magnetic resonance imaging, and magnetic resonance spectroscopy, near-infrared spectrometry (NIRS)-monitored regional cerebral oxygen saturation (rScO 2 ) is increasingly used (1)(2)(3). NIRS is a noninvasive, bedside technique which can be used to monitor mixed cerebral saturation, which correlates well with venous jugular bulb saturation (4)(5)(6) and estimates oxygen supply to the brain (1,2). Normal values of rScO 2 in the neonatal brain are reported to range from 55 to 85% (2,(4)(5)(6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides continuous electroencephalogram monitoring, cranial ultrasound, magnetic resonance imaging, and magnetic resonance spectroscopy, near-infrared spectrometry (NIRS)-monitored regional cerebral oxygen saturation (rScO 2 ) is increasingly used (1)(2)(3). NIRS is a noninvasive, bedside technique which can be used to monitor mixed cerebral saturation, which correlates well with venous jugular bulb saturation (4)(5)(6) and estimates oxygen supply to the brain (1,2). Normal values of rScO 2 in the neonatal brain are reported to range from 55 to 85% (2,(4)(5)(6).…”
mentioning
confidence: 99%
“…NIRS is a noninvasive, bedside technique which can be used to monitor mixed cerebral saturation, which correlates well with venous jugular bulb saturation (4)(5)(6) and estimates oxygen supply to the brain (1,2). Normal values of rScO 2 in the neonatal brain are reported to range from 55 to 85% (2,(4)(5)(6).…”
mentioning
confidence: 99%
“…Misra et al (15), using INVOS 3100, recorded a mean CO value of 67.2% ± 8.4%. Yoshitani et al (16), using INVOS 4100 and NIRO 300, found a mean CO value of 66% ± 8% and 66% ± 7%, respectively. In a study of 31 infants, Aldrich et al (17) detected the mean value of CO measured within 30 minutes after delivery as 22-73%.…”
Section: Discussionmentioning
confidence: 99%
“…The overall bias of )2.1% with wide limits of agreement (1.96 SD limit of agreement of 14.7%) makes interpretation of the absolute values of TOI and rSO 2 difficult and adds to the debate Figure 1 Schematic representation of the study protocol. [15]. The wide limits of agreement suggest that the absolute values for rSO 2 and TOI may be too imprecise for clinical use.…”
Section: Discussionmentioning
confidence: 99%